Evaluation of user satisfaction concerning Spatial organization in public open space - Shafique , Adiba; Abdul Majid, Roshida (International Journal of Psychosocial Rehabilitation, 2020)
The research paper examines the level of users satisfaction regarding spatial organization in Indian public open space. Moreover, for comprehensive investigation, it also seeks to explore the difference in responses between gender and age group. The methodology of research includes quantitative method with questionnaire-based survey, evaluate by using ‘Likert scale’ ranging from 1 to 5 i.e. from ‘strongly disagree’ to ‘strongly agree'. The three public open spaces of New Delhi have been selected as a case study. The output of the study is validated through univariate statistical tools including mean and standard deviation, whereas for analyzing difference in responses between male and female, different age group, T-test and one-way ANOVA has been performed, respectively. The finding contributes to determine the outlook of user’s satisfaction for present spatial organization of Public open space. Further, the study concludes that the user’s response is between unsatisfied to neutral which implies that spatial organization in Indian public open space needs improvement as per users necessity.